2021
DOI: 10.1029/2021av000395
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Response to the 2019 Ridgecrest Earthquake With Distributed Acoustic Sensing

Abstract: Rapid seismic deployments after major earthquakes often produce critical data for characterizing postseismic processes. Taking advantage of pre‐existing optical fibers, the recently emerging distributed acoustic sensing (DAS) technology can quickly establish ultra‐dense seismic arrays after the mainshocks. Here we present the first example of such a rapid‐response experiment using four telecommunication fiber optic cables near the 2019 M 7.1 Ridgecrest earthquake in California. By applying template matching to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 31 publications
0
34
0
Order By: Relevance
“…Our continuous DAS array also allows us to image the near-surface structure that may be the cause of the S wave amplification pattern observed above. While numerous aftershocks were recorded (Li et al, 2021), the continuous data are still dominated by urban noise from vehicles with weekly periodicity (Figure S3 in Supporting Information S1), due to the proximity of the cable to Highway 395. With cross-correlations stacked over three months, the Rayleigh wave fundamental mode can be clearly tracked, with the asymmetric bending of arrival times suggesting strong velocity variability (Figure 2a).…”
Section: Subsurface Imaging With Traffic Noisementioning
confidence: 99%
“…Our continuous DAS array also allows us to image the near-surface structure that may be the cause of the S wave amplification pattern observed above. While numerous aftershocks were recorded (Li et al, 2021), the continuous data are still dominated by urban noise from vehicles with weekly periodicity (Figure S3 in Supporting Information S1), due to the proximity of the cable to Highway 395. With cross-correlations stacked over three months, the Rayleigh wave fundamental mode can be clearly tracked, with the asymmetric bending of arrival times suggesting strong velocity variability (Figure 2a).…”
Section: Subsurface Imaging With Traffic Noisementioning
confidence: 99%
“…As already noted, the surface location of the optical cable makes it possible to register technogenic microseisms, and local and teleseismic earthquakes, including extremely low-frequency ones. In recent years, many researchers have been engaged in registering earthquakes using DAS [ 135 , 136 , 137 , 138 , 139 ].…”
Section: Das In Geophysics (Boris G Gorshkov)mentioning
confidence: 99%
“…Li & Zhan (2018) showed that template matching could be successfully applied to DAS data. This technique has been modified to perform template matching using the Ridgecrest DAS array to supplement the Southern California Seismic Network's (SCSN) catalogue of Ridgecrest earthquake aftershocks (Li et al 2021). Though this catalogue is successful in improving the number of catalogued events, the template matching catalogue contains diurnal depressions in the number of events due to cultural noise.…”
Section: Template Matchingmentioning
confidence: 99%
“…Though median filtering mitigates this issue, these artefacts are often unavoidable. An adaptive spectrum screening algorithm can potentially help better separate earthquake signals from coherent noise, but for consistency with the original template matching framework, we bandpass filter each station between 2 and 8 Hz (Li et al 2021).…”
Section: Template Matchingmentioning
confidence: 99%